The effectiveness of Problem Management Plus at 1-year follow-up for Syrian refugees in a high-income setting - Anne M. de Graaff; Pim Cuijpers; Mariam Elsawy; Sam Hunaidy; Barbara Kieft; Noer Gorgis; Jos W. R. Twisk; Yenovk Zakarian; Theo K. Bouman; Miriam J. J. Lommen; Ceren Acarturk; Richard Bryant; et al. (Cambridge University Press, 2024)
Abstract Aims Problem Management Plus (PM+) has been effective in reducing mental health problems among refugees at three-month follow-up, but there is a lack of research on its long-term effectiveness. This study examined the effectiveness of PM+ in reducing symptoms of common mental disorders at 12-month follow-up among Syrian refugees in the Netherlands. Methods This single-blind, parallel, controlled trial randomised 206 adult Syrians who screened positive for psychological distress and impaired functioning to either PM+ in addition to care as usual (PM+/CAU) or CAU alone. Assessments were at baseline, 1 week and 3 months after the intervention and 12 months after baseline. Outcomes were psychological distress (Hopkins Symptom Checklist [HSCL-25]), depression (HSCL-25 subscale), anxiety (HSCL-25 subscale), posttraumatic stress disorder symptoms (PCL-5), functional impairment (WHODAS 2.0) and self-identified problems (PSYCHLOPS). Results In March 2019-December 2022, 103 participants were assigned to PM+/CAU and 103 to CAU of which 169 (82.0%) were retained at 12 months. Intention-to-treat analyses showed greater reductions in psychological distress at 12 months for PM+/CAU compared to CAU (adjusted mean difference −0.17, 95% CI −0.310 to −0.027; p = 0.01, Cohen's d = 0.28). Relative to CAU, PM+/CAU participants also showed significant reductions on anxiety (−0.19, 95% CI −0.344 to −0.047; p = 0.01, d = 0.31) but not on any of the other outcomes. Conclusions PM+ is effective in reducing psychological distress and symptoms of anxiety over a period up to 1 year. Additional support such as booster sessions or additional (trauma-focused) modules may be required to prolong and consolidate benefits gained through PM+ on other mental health and psychosocial outcomes.